Association between substance use and PrEP adherence among adolescent girls and young women enrolled in an HIV prevention study in Southern Africa. - Kudzai Hlahla; Rahul Paul Choudhury; Bekezela Siziba; Peter L Anderson; Sinead Delany-Moretlwe; Theodorah Rirhandzu Ndzhukule; Sybil Hosek; Nyaradzo M Mgodi; on behalf of the HPTN 082 Study Team (PLOS Global Public Health)
Adolescent girls and young women (AGYW) in sub-Saharan Africa are at substantial risk of HIV acquisition and could benefit from oral pre-exposure prophylaxis (PrEP) for HIV prevention. Substance use may result in poor adherence, diminishing PrEP effectiveness. The effects of substance use on PrEP adherence in AGYW within the African context have not been extensively studied. We sought to determine the prevalence of substance use and its association with PrEP adherence in AGYW enrolled in an HIV prevention trial. The HIV Prevention Trials Network (HPTN) 082 study enrolled healthy, HIV-negative, sexually active young women (16-25 years) from Cape Town, Johannesburg, South Africa, and Harare, Zimbabwe, between October 2016-2018. Participants were offered oral PrEP. Data on hazardous drinking was collected using the AUDIT-C questionnaire and defined as having an AUDIT-C score ≥3. Data on substance use was collected using the abridged ASSIST questionnaire, with responses categorized as 0 (never used a substance) and 1 (ever substance use). Tenofovir-diphosphate (TFV-DP) levels in dried blood spots at weeks 13, 26, and 52 were used to measure PrEP adherence. Low adherence was defined as TFV-DP concentration <700 fmol/punch. Repeated measure multinomial regression modeling was used to determine associations between substance use and hazardous drinking vs PrEP adherence. Of the 451 participants enrolled, 427 (95%) initiated PrEP. The prevalence of hazardous drinking and substance use at baseline was 37% and 24%, respectively. Hazardous drinking was highest in Cape Town (53%). Substance use was highest in Johannesburg (31%). Cannabis (7%) and sedatives (6%) were the most frequently used substances. Hazardous drinking (aOR=1.55, 95%CI = 1.05-2.29) was associated with increasing odds of low PrEP adherence. Substance use was not associated with low PrEP adherence. There is a need for increased screening for hazardous drinking and substance use and its integration within PrEP programs in AGYW in Africa.